EDUKASI PENCATATAN DAN PEMBUKUAN SEDERHANA PADA KERAJINAN SONGKET SILUNGKANG DEMI MEWUJUDAKAN WIRAUSAHA FROM LOCAL TO GLOBAL - Siska Yulia Defitri; Juita Sukraini; Rita Dwi Putri; Witra Maison; Nidia Anggreni Das; Lili Wahyuni; Aldo Sofari; Desrial Ori Putra (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
Micro, Small and Medium Enterprises (MSMEs) are an important part of the national economy, but not all MSMEs have the ability to make financial reports. Meanwhile, financial statements provide benefits in describing business conditions. The purpose of the service is to provide education to MSMEs in this case the Silungkang Songket Craft so that they can understand and make simple financial reports at least. The method of devotion is carried out by providing materials and direct training in front of the Silungkang Songket Craft business actors. The hope of this service is that these business actors can make strategic decisions in an effort to develop their business from a local to a global level through the financial information available in the bookkeeping of financial statements